2013
DOI: 10.1152/ajpgi.00387.2012
|View full text |Cite
|
Sign up to set email alerts
|

PAR-2-mediated control of barrier function and motility differs between early and late phases of postinfectious gut dysfunction in the rat

Abstract: Fernández-Blanco JA, Hollenberg MD, Martínez V, Vergara P. PAR-2-mediated control of barrier function and motility differs between early and late phases of postinfectious gut dysfunction in the rat. Am J Physiol Gastrointest Liver Physiol 304: G390 -G400, 2013. First published December 13, 2012; doi:10.1152/ajpgi.00387.2012.-Proteinase-activated receptor-2 (PAR-2) and mast cell (MC) mediators contribute to inflammatory and functional gastrointestinal disorders. We aimed to characterize jejunal PAR-2-mediated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 46 publications
6
32
0
Order By: Relevance
“…After the infection, animals were regularly monitored for clinical signs and body weight changes. Normal course of the infection was confirmed by a significant decrease of body weight in infected animals compared with controls, with a peak reduction on days 8-10 PI and a subsequent linear increase over time, as previously described by us [9,10].…”
Section: Trichinella Spiralis Infectionsupporting
confidence: 76%
See 2 more Smart Citations
“…After the infection, animals were regularly monitored for clinical signs and body weight changes. Normal course of the infection was confirmed by a significant decrease of body weight in infected animals compared with controls, with a peak reduction on days 8-10 PI and a subsequent linear increase over time, as previously described by us [9,10].…”
Section: Trichinella Spiralis Infectionsupporting
confidence: 76%
“…Muscle-stage larvae of T. spiralis were obtained from infected CD1 mice as previously described [9,10]. Rats were infected at 7-8 weeks of age by administration of 7500 T. spiralis larvae, suspended in 1 ml of saline by oral gavage.…”
Section: Trichinella Spiralis Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we have described a similar increase in CTMCs in the jejunum of Trichinella spiralis-infected rats, an accepted model of post-infectious IBS that also courses with dysmotility. 33 Moreover, CTMC counts are increased in mice with food allergy 34,35 and the degranulation of CTMCs excites the intestinal smooth muscle in vitro. 36 Although further in deep studies are required, these observations suggest that submucosal CTMC could be taking part in the altered contractile responses observed in OVA-LPS-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells have been widely studied in IBS patients and several animal models; for example, mast cell tryptase increased epithelial permeability and intestinal barrier dysfunction in a PAR2-mediated manner. 38 Lee et al 39 found that rectal mucosal mast cell count was significantly correlated with intestinal permeability in IBS-D patients, which indicated mucosal mast cells to play an important role for increased permeability in patients with IBS-D. As an important component of the innate immune system, mast cells also play a significant role in immune disorders in the gut and especially in the neuro-immune interaction that may be involved in the development of visceral hyperalgesia. Previous study by Yu et al 40 demonstrated that mast cell activation induced long-lasting mechanical hypersensitivity of nodose C-fibers in the guinea pig esophagus and mast cell trypase played an important role in this sensitization process.…”
Section: Discussionmentioning
confidence: 99%